Diabetic Ketoacidosis In Children With Type 1 Diabetes : A Comprehensive Literature Review - Dewi, Astridena Narulita (The International Journal of Medical Science and Health Research, 2024)
Introduction: Diabetic ketoacidosis (DKA) is a critical condition often encountered in pediatric patients with type 1 diabetes. Objective: This review aims to summarize current strategies and guidelines for managing pediatric diabetic ketoacidosis (DKA), focusing on fluid resuscitation, insulin therapy, and long-term outcomes. Methods: A comprehensive review of recent literature from the past decade was conducted. Key studies were selected based on their relevance to pediatric DKA management, particularly regarding fluid resuscitation methods and insulin regimens. Results: The review highlights that effective management of pediatric DKA requires a balance of fluid resuscitation and insulin therapy. Recent studies emphasize the importance of using a structured clinical pathway to improve outcomes and reduce complications. Conclusion: Proper management of pediatric DKA involves timely recognition, appropriate fluid resuscitation, and insulin therapy, with a focus on monitoring for complications such as cerebral edema. The use of structured clinical pathways and liberal fluid administration in the absence of cerebral edema are supported by recent evidence to improve patient outcomes.